The Atis of Camiros, Anilao, Iloilo their culture as influenced by the outside world - Dable, Nelve A.
This is an ethnographic study exploring the culture of the Atis of Camiros, Anilao. It aims to: 1)trace the origin and development of the Ati settlement in Camiros, Anilao; 2)determine the socio-cultural, political, economic and religious changes that took place within their community and to identify the factors that brought about these gradual changes; 3)give description of the Atis' present way of living in Camiros, Anilao; 4)determine or manifestation of modernization on their lives; 5)identify the existing culture that they still practice; and 6) discuss the problems that confronted them as a minority community., Information is primarily taken from interviews with key respondents using an interview guide as a research tool. Key informants are identified members of the Ati community. The researcher had also made an observation on the Atis' way of living, record her findings and conducted an informal interview with the Atis to supplement and to verify the observation. The study provides a description of the changes in different aspects of Atis' life overtime and how external influences caused such changes. In particular, the study looks at the influences brought by the Bisaya people, the dominant people in the place. The frequent contact and constant interaction of this people with the Bisaya bring about the acculturation of this people to the mainstream society; Atis embrace the practices, beliefs, norms, values, and life ways of the dominant Bisaya culture. The alteration of their indigenous living further enhanced by their adoption of the Christian faith.